2018
DOI: 10.1016/j.ijpsycho.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Challenge and threat states: examining cardiovascular, cognitive and affective responses to two distinct laboratory stress tasks

Abstract: The TCTSA is supported during competitive stress, however during social stress there is dissociation between self-report appraisals and cardiovascular reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(46 citation statements)
references
References 46 publications
2
43
1
Order By: Relevance
“…Moreover, Dixon et al (2019) showed that challenge CV reactivity positively predicted future soccer performance (rated by players and coaches), but that athletes with a blunted CV response performed worse than challenge and threat responders and that there was a weak association between self-report data and cardiovascular responses. Interestingly, the findings of Trotman et al (2018) show support for the central tenets of the TCTSA during competitive stress, but not social stress. This suggests that the type of task may have an impact on the relationship between resource appraisals and cardiovascular reactivity, and that blunted cardiovascular responses need to be considered (see also Wormwood et al, 2019).…”
Section: The Predictions Of the Theory Of Challenge And Threat Statesmentioning
confidence: 82%
See 3 more Smart Citations
“…Moreover, Dixon et al (2019) showed that challenge CV reactivity positively predicted future soccer performance (rated by players and coaches), but that athletes with a blunted CV response performed worse than challenge and threat responders and that there was a weak association between self-report data and cardiovascular responses. Interestingly, the findings of Trotman et al (2018) show support for the central tenets of the TCTSA during competitive stress, but not social stress. This suggests that the type of task may have an impact on the relationship between resource appraisals and cardiovascular reactivity, and that blunted cardiovascular responses need to be considered (see also Wormwood et al, 2019).…”
Section: The Predictions Of the Theory Of Challenge And Threat Statesmentioning
confidence: 82%
“…Overall, there is mixed evidence to support the proposed relationships between the resource appraisals (self-efficacy, perceptions of control, achievement goals), cardiovascular indices of challenge and threat, and emotions. Some published studies support the proposed relationships (Trotman et al, 2018), whereas others do not (Turner et al, 2012(Turner et al, , 2013Dixon et al, 2019). Indeed, in one study, higher levels of self-efficacy were associated with a threat state, which is contrary to the TCTSA (Meijen et al, 2014).…”
Section: The Predictions Of the Theory Of Challenge And Threat Statesmentioning
confidence: 88%
See 2 more Smart Citations
“…12 It is particularly interesting that the intensity of the emotional response to a competition did not differ, despite the fact that some teams regarded the competition as more of a challenge; this is in line with some previous research. 15,16 It has been hypothesised that anxiety states may be seen as more helpful in those who appraise a scenario as challenging, but we did not collect data on participants' perceptions of emotional states in the present study.…”
Section: Discussionmentioning
confidence: 96%